Recent Findings in the Regulation of Programmed Death Ligand 1 Expression - Shen, Xiangfeng; Zhang, Lihong; Li, Jicheng; Li, Yulin; Wang, Yishu; Xu, Zhi-Xiang (Frontiers in Immunology, 2019)
With the recent approvals for the application of monoclonal antibodies that target the well-characterized immune checkpoints, immune therapy shows a great potential against both solid and hematologic tumors. The use of these therapeutic monoclonal antibodies elicits inspiring clinical results with durable objective responses and improvements in overall survival. Agents targeting programmed cell death protein 1 (PD-1; also known as PDCD1) and its ligand (PD-L1) achieve a great success in immune checkpoints therapy. However, the majority of patients are failed to respond to PD-1/PD-L1 axis inhibitors. Expression of PD-L1 on the membrane of tumor and immune cells has been shown to be associated with enhanced objective response rates to PD-1/PD-L1 inhibition. Thus, understanding of how PD-L1 expression is regulated will enable us to better define its role as predictive marker. In this review, we summarize recent findings in the regulation of PD-L1 expression.